2011
DOI: 10.1007/s10698-011-9123-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry, a lingua philosophica

Abstract: We analyze the connections of Lavoisier system of nomenclature with Leibniz's philosophy, pointing out to the resemblance between what we call Leibnizian and Lavoisian programs. We argue that Lavoisier's contribution to chemistry is something more subtle, in so doing we show that the system of nomenclature leads to an algebraic system of chemical sets. We show how Döbereiner and Mendeleev were able to develop this algebraic system and to find new interesting properties for it. We pointed out the resemblances b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…That is, teachers need to lay an emphasis on the functions when offering instructions on the complex convention of symbolism (and other forms of technical representation). It is reported that educators have recently attempted to help young students to familiarise themselves with symbolism by comparing it with natural language (e.g., Goodney, 2006;Restrepo and Villaveces, 2011;Cadeddu et al, 2014). This comparison can be productive, because Berzelian notations had a linguistic origin.…”
Section: Implications For Teaching and Learning Chemistrymentioning
confidence: 99%
“…That is, teachers need to lay an emphasis on the functions when offering instructions on the complex convention of symbolism (and other forms of technical representation). It is reported that educators have recently attempted to help young students to familiarise themselves with symbolism by comparing it with natural language (e.g., Goodney, 2006;Restrepo and Villaveces, 2011;Cadeddu et al, 2014). This comparison can be productive, because Berzelian notations had a linguistic origin.…”
Section: Implications For Teaching and Learning Chemistrymentioning
confidence: 99%